Outcome of care provided in neonatal surgery intensive care unit of a public sector tertiary care teaching hospital of India - Vijaydeep Siddharth; Shakti Kumar Gupta; Sandeep Agarwala; Sidhartha Satpathy; Prabudh Goel (Wolters Kluwer Medknow Publications, 2019)
Aims: There is limited literature on the outcome of care in intensive care units (ICUs), especially when it comes to neonatal surgical units. Hence, this study was aimed to observe the outcome of care provided in the neonatal surgery ICU (NSICU) at an apex tertiary care teaching institute of North India. Methods: A descriptive, observational study was carried out through retrospective medical record analysis of all the patients admitted in NSICU from January to June 2011. Results: In NSICU, from January to June 2011, 85 patients were admitted. More than two-third (69.9%) patients were admitted through the emergency department. Of the total admitted patients, 69.9% were male. Mean and median age of the admitted patients were 6.31 and 2 days (range 0-153 days), respectively. The most common diagnosis was esophageal atresia with tracheoesophageal fistula (36.1%).Within a day of admission at NSICU, 88% patients underwent surgical intervention. Of the total admitted patients, 56.6% required mechanical ventilation with 3.57 days (range 0-31 days) of mean duration of mechanical ventilation. Reintubation rate (within 48 h of extubation) was observed to be 15.7%, and 27.7% (23) of the patients required vasopressor support during their NSICU stay. Patients who developed postoperative complications were 34.25%, with the most common being wound infection/discharge/dehiscence. Two patients were readmitted within 72 h of their discharge/transfer out from the NSICU. Conclusion: NSICU survival rate was 85.5% and net death rate was observed to be 14.5%. Sepsis was the major reason for mortality in NSICU.